Effects of potassium on the inhibitory effect of gossypol on Na,K-ATPase in vitro - BI Xiao-feng; ZHENG Yun-juan; LIANG Duan; YANG Hui-fen (Acta Pharmacologica Sinica, 2016)
This paper reports the following characteristics of the inhibitory effect of gossypol acid on Na+, K+-ATPase activity in vitro: 1. Gossypol acetic acid 20μg/ml inhibited Na+, K+-ATPase rapidly and obviously. 2. Inhibitory effects of gossypol(100μg/ml) on Na+, K+-ATPase was reversed by decreasing the concentration of gossypol to 10μg/ml or increasing that of K+ (from 0.5 to 10 Mm). 3. The inhibition for K+-ATPase appeared to be non-competitive.